Predicted thermodynamic structural and elastic properties of SrCuP and SrCuSb for thermoelectric applications - N. Bioud; N. Benchiheub; A. Benamrani; M. A. Ghebouli; M. Fatmi; Faisal Katib Alanazi; R. Yekhlef (Scientific Reports)
Abstract The Pseudopotential method coupled with plane waves implemented in the quantum espresso code was used in the prediction of the structural parameters and elastic constants of SrCuX (X = P, Sb) materials. The obtained results of lattice parameters and bulk modulus at equilibrium agree well with their experimental and theoretical data cited in the literature. The calculated Young’s modulus of SrCuX (X = P, Sb) aggregate thermoelectric materials are 109.25 GPa and 78.22 GPa, while their Debye temperatures are 364.2 K and 261.8 K. The vibration energy of phonons is 24.14 kJ/mol and 23.37 kJ/mol for SrCuP and SrCuSb. Our thermodynamic parameters increase monotonically with temperatures for both SrCuP and SrCuSb materials. To the best of our knowledge, there are no data available in the literature on the elastic and thermodynamic parameters of SrCuX (X = P, Sb) compounds, then our results are prediction. The absence of virtual phonon frequencies indicates high dynamic stability in both materials, with a band gap about 1 THz between optical and acoustic phonons in SrCuP and SrCuSb.